Permanent neonatal diabetes mellitus presenting with mixed diabetic ketoacidosis and hyperglycemic hyperosmolar state, a diagnostic and therapeutic challenge - Dutta, Arpita; Bhattacharya, Urmimala; Bhakta, Subhajit; Pal, Dilip Kumar (Indian Journal of Case Reports, 2024)
Neonatal diabetes mellitus (NDM) is a rare metabolic disorder affecting 1 in 90,000–1,60,000 live births. Diabetic ketoacidosis (DKA) and hyperglycemic hyperosmolar state (HHS) are the most serious and potentially fatal complications in patients with diabetes. Although considered two separate entities along the spectrum of hyperglycemic emergencies, they can coexist as a clinical presentation. Neonatal presentations of both these entities are extremely rare, and a mixed presentation is sparsely reported. We describe a rare case of a 42-day-old male infant, initially presenting with severe shock and sepsis, later diagnosed as a mixed presentation of DKA and HHS, in permanent NDM. Genetic analysis denoted autosomal dominant KCNJ-11 mutation encoding Kir6.2 subunit of K-ATP channel as the sole etiological factor. Very few case reports of mixed presentation of DKA and HHS in NDM are available. Early recognition of this rare presentation and prompt management reduce mortality. Genetic diagnosis is important as children with mutated K-ATP channels respond well to oral sulfonylurea therapy.